Application Design of the Medicines Usage Prediction Based on Backpropagation Neural Network Method and PHP - I Putu Arya Dharmaadi; Gusti Made Arya Sasmita (Journal of Information Technology and Its Utilization, 2019)
The development of information technology makes many organizations utilizing it in their business process. For example, hospitals use certain information systems in medicine management. We observe that most medicines applications do not provide the drug usage prediction feature so that this situation causes the hospital staff being difficult in providing enough medicines. Therefore, in this experimental research, we developed an application in the form of a simple design for helping the hospitals in predicting daily medicine usage. This application also provides medicines stock management and doctor diagnosis features. The Brainy library is used to facilitate implementing the backpropagation neural network method in PHP programming language. We choose PHP because this server script is widely used in information system development. We demonstrated that the mock-up as the result of this development is able to work properly. For further study, we suggest expanding this mock-up become a full hospital information system that covers many functions in medical centers.